Predation and the evolution of multicellularity - Kapsetaki, S (2015)
The first step in the major evolutionary transition to multicellularity involves single cells forming a group. Why do cells form a group? Studies have shown that colony formation provides a benefit against predation. However, it is not well known whether this response is generic, or specific to certain prey-predator systems. We sought to assess this by measuring colony formation in nine 'algal-putative predator' combinations; the Chlorophyte algae Chlorella vulgaris, Chlorella sorokiniana and Scenedesmus obliquus as prey, and the flagellate Ochromonas spp., the ciliate Tetrahymena thermophila and the crustacean Daphnia magna as putative predators. We found that colony formation is a generic response of the algae C. sorokiniana, C. vulgaris and S. obliquus to predation by Ochromonas spp., T. thermophila or D. magna. Notably, the algae formed colonies regardless of whether the putative predator grazed upon the algae, indicating that predation by itself is not always a prerequisite for colony formation, but this response may have evolved in the algae as a defensive mechanism against potential predation. In six combinations, colonies could not be ingested by the predator, suggesting that colonies have a 'size benefit' against predation. These results outline the importance of predation as a generic factor driving colony formation and help enhance our understanding of the benefits and costs involved in colony formation, the first step in the evolution of multicellularity.